Determinan keputusan investasi dengan moderasi financial attitude pada IAI Muda Jawa Timur - Yuliani, Indrianti; Setyowati, Supami Wahyu; Irianto, Mochamad Fariz (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
This study aims to determine the influence of the determinants of investment decisions consisting of financial knowledge, financial well-being, risk tolerance with moderation of financial attitudes. The population and research sample used a saturated sample technique with a total of 194 East Java Young Indonesian Accountants' Associations with various commissariats in it. Data analysis used the Partial Least Suare (PLS) approach with the help of Smart PLS 3.0 software. This research shows that financial knowledge, financial well-being, risk tolerance with moderation of financial attitudes have an influence on investment decisions.